DETERMINATION OF RADIONUCLIDES IN SOIL FROM BARENDRA REGION IN RAJSHAHI AND MINING REGION IN DINAJPUR - Rahman, M Matiur; Begum, Aleya; Ferdous, Mst. Jannatul; Islam, M Aminul (Malaysian Journal of Science, 2013)
The level of natural radioactivity in soil samples calculated from the Barendra region, Rajshahi and the Mining region, Dinajpur was measured and the radiological hazard parameters in both the regions were estimated. The activity concentrations of naturally occurring radioactive materials in the 238U and 232Th decay chains and in 40K were determined by means of a gamma-ray spectrometry system using an HPGe detector in a low background configuration at Atomic Energy Centre, Dhaka. The activity concentrations of 238U, 232Th and 40K found in the present study are compared with the reported values of the Northern region and other districts of Bangladesh and those of other countries of the world. Radiological hazard parameters of the two regions were estimated and compared with the world averages. The natural radioactivity in the Barendra and Mining region poses no threat to general public there. Artificial radionuclide 137Cs was not found in the soil samples studied. (Keywords: Radioactivity, HPGe Detector, Soil, Barendra and Mining region, Radiological hazard parameters)